WHY MUSLIM STUDENTS PLAGIARIZE IN WRITING ENGLISH TEXTS - Nashruddin, Wakhid (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2013)
Reasons for copy-pasting someone elseâs works has attracted attention from many sides that copy-pasting activities, or more popular with term plagiarism, have been considered as a threat for academic life. It also happens at the case of muslim students, in which Islam teaches the students to be honest and not to steal from others. For understanding why it happens, this exploration is conducted. The students of English Department of IAIN Syekh Nurjati Cirebon have to write many of their assignments in English. The result of my observations, the quality of the studentsâ writing is not good enough. One of the cases found is the copy-paste works, or plagiarism. Using interviews instrument, I try to figure out why students of English Department of IAIN Syekh Nurjati Cirebon. There are at least three reasons behind why students act plagiarism; ignorance on the quotation and citation rules, poor writing skills, and the need of instant writing result. This paper tries to explore these reasons.Keywords: copy-paste, plagiarism, writing in English